Analysis of the Implementation of Administrative Development Policy: Case Study in Dili Municipality - Santino Barros; Samuel Carlos Ribeiro (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to find out the legal framework for the establishment of local power seen from human resources and the budget executed in the pilot administrative decentralization policy. The theory that local governance and administrative decentralization and the methods used in this research are qualitative descriptive. From the first constitutional to the present, the central government has started with several efforts through the referendum package, PDD I and PDD II and the other and ultimately the implementation of the administrative decentralization pilot policy which has been carried out gradually through the direct administration of indirect administration and the preparation of the institutional administrative decentralization and finally the decision-making of Law No.23/2021 on local power and public administrative decentralization has been intended or not to allow the law to be carried out in order to resolve the wishes of the municipal people. Therefore the maximum effort is needed to recruit the specialized people to help carry out the decentralization policy properly in order to calm the role of the central government by sharing the power and competence of the Municipal Authority which is concentrated as a process of administrative autonomy in more than nine hundred competencies consisting of development with a amount of less than five thousand dollars ($500.00), a minor capital of less than one hundred thousand US dollars ($150.00) is appropriate to the President of the Municipal Authority and the Municipal Administrator who sign up and ultimately increases the report to the Ministry of Finance. The central government has now also delegated competencies on operational services/key tasks such as: health, agriculture, infrastructure through (PNDS, UNP) sports and others. Part of the sport has almost completely handed over money and goods. The Ministry of State Administration has handed over the procurement directorate so that the municipality can handle it itself but when technical support is needed from the national level it only provides technical support. All of these processes can lead to a good life.